2021
DOI: 10.1111/rec.13558
|View full text |Cite
|
Sign up to set email alerts
|

Canopy cover and ecological restoration increase natural regeneration of rainforest trees in the Western Ghats, India

Abstract: Restoration of canopy cover through tree planting can assist in overcoming barriers to natural regeneration and catalyze recovery of degraded tropical forests. India has made international pledges to restore millions of hectares of degraded forests by 2030, but lacks empirical research on regeneration under different types of planted and natural overstories to guide this mission. We conducted a field study (65 plots of 25 m2) to examine the influence of overstory type and canopy cover on naturally regenerating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…While the co‐benefits of biodiversity recovery during silvicultural approaches for biomass recovery are often presumed (Crouzeilles et al., 2017; Hariharan & Shankar Raman, 2022; Osuri et al., 2022), it remains unknown whether active restoration through these means delivers recovery of the reference community assemblage. Our study shows that 15–27 years after implementation of active restoration via rehabilitative silvicultural treatments in the logged forests, the richness and evenness of seedling communities were higher than those in adjacent NR forests and more closely resembled those of the seedling communities in UL forest, while nonetheless remaining distinct from these, in the initial 2 months after masting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the co‐benefits of biodiversity recovery during silvicultural approaches for biomass recovery are often presumed (Crouzeilles et al., 2017; Hariharan & Shankar Raman, 2022; Osuri et al., 2022), it remains unknown whether active restoration through these means delivers recovery of the reference community assemblage. Our study shows that 15–27 years after implementation of active restoration via rehabilitative silvicultural treatments in the logged forests, the richness and evenness of seedling communities were higher than those in adjacent NR forests and more closely resembled those of the seedling communities in UL forest, while nonetheless remaining distinct from these, in the initial 2 months after masting.…”
Section: Discussionmentioning
confidence: 99%
“…While the co-benefits of biodiversity recovery during silvicultural approaches for biomass recovery are often presumed (Crouzeilles et al, 2017;Hariharan & Shankar Raman, 2022;Osuri et al, 2022), it remains unknown whether active restoration through these means delivers recovery of the reference community assemblage.…”
Section: F I G U R Ementioning
confidence: 99%
“…While we did not deliberately manipulate shade-tolerance in our planting, other restoration projects have found that it is possible to facilitate forest recovery by planting shade-intolerant species initially and then allowing natural recruitment of shade-tolerant species in the understory (Osuri et al 2022). This can increase planting survival and reduce the costs of planting by requiring the planting of fewer species (Brancalion et al 2019).…”
Section: Species Identity Rather Than Diversity Metrics Explain Most ...mentioning
confidence: 99%
“…This paper provides brief information on the rehabilitation of highly degraded lands with trees, bioenergy crops, diversified cropping systems, man-made forests, and agroforestry models investigated as ecological restoration models to be adopted for various socioeconomic goals. Osuri et al (2022), on the restoration of degraded rainforests in the Western Ghats of India, show that restoration through diverse native species can help recovery to a very close state to the reference ecosystem compared to monoculture plantations. The authors conducted field studies in a large area within a tropical rainforest ecosystem to investigate the effect of top story canopy cover (which plays a vital role in shaping ground story vegetation) on regeneration of native tree seedlings in degraded rainforests, forest under ecological restoration with mixed-native species, single-species forest stands, and a reference mature rainforest.…”
Section: Review and Synthesis Of Papers In This Sectionmentioning
confidence: 99%